**3a + b = 3ab****2s + 4t = 6st**

Do you think Jane is correct in her algebraic manipulations?

If yes, please write down examples to show that her answer is correct.

If not, explain to Jane her mistakes and help her to correct.

*Enter your response in Comments.*

Nope, she is wrong.

ReplyDelete3a+b=3a+b

2s+4t=2s+4t

The expressions are already simplified. So, she is wrong~~~

She is wrong.

ReplyDelete3a + b should be 3a+b as it cannot be simplified further .

2s + 4t should be 2s + 4t as it cannot be simplified further .

Jane's answer is equivalent to 3*a*b as ab also means a*b and 6st will also mean 6*s*t.

Nope. As all expressions are already simplified.

ReplyDelete3a + b = 3a+b.

a and b are different unknown numbers.

According to Jane's answer(3ab), the correct explanation is 3 times of a multiply by b,which is, 3*a*b.

The same thing for 2s +4t. Same explanation.

I think that she is wrong.

ReplyDelete3a+b is already simplified. 3ab is actually 3 x ab which is wrong in this expression.

2s+4t is already simplified. 6st is 6 x st which is wrong.

She is wrong. 3a+b = 3a+b while 3ab=3xab or 3 x a x b. And the same goes for 2s + 4t.

ReplyDeleteShe is wrong. 3a+b is 3*a+b but 3ab is 3*a*b.

ReplyDeleteAlso, 2s+4t is equal to 2*s+4*t but 6st is 6*s*t.

I think she is wrong as the above expressions are already simplified and cannot be simplified further.Plus s and t are different numbers and cannot be mixed together.

ReplyDeleteCorrection for Jane: 3a+b= 3a+b

ReplyDelete2s+4t=2s+4t

She is wrong because ab and st means a*b and s*t but Jane is adding them so she should leave it as 3a+b and 2s+4t. Putting numbers beside unknowns or unknowns beside unknowns also causes people to mistake them as the coefficients of the unknown.

ReplyDeleteI think Jane is wrong.

ReplyDeleteThe correct answers are: 3a+b=3a+b, 2s+4t=2s+4t.

3a+b and 2s+4t are expressions, not equations.

~Nina

This comment has been removed by the author.

ReplyDeleteNo, she is not correct.

ReplyDelete3ab is equal to 3*a*b, whereas it should equal to 3*a+1*b.

6st is equal to 6*s*t, whereas it should equal to 2*s+4*t.

She should leave the expressions as 3a+b and 2s+4t respectively as they cannot be simplified further.

She is wrong.

ReplyDelete3a+b is equal to 3 sets of a plus b. But her answer is 3ab which is 3 sets of a times b which is wrong.

2s+4t is equal to 2 sets of s plus 4 sets of t. But her answer is 6st which is 6 sets of s times x.

These 2 question cannot be solved unless we know the variable.

Im Gladys (:

3a + b = 3ab

ReplyDelete2s + 4t = 6st

3ab actually means 3*a*b which is different from 3*a+b

6st actually means 6*s*t which is different 2s+4t

Lovy Lim

ps. forgot to answer the main question...yup, that guy or girl is wrong

ReplyDeleteNope, she is totally wrong.

ReplyDelete3a*b=3*ab which is 3ab BUT 3a+b=3a+b

2s*4t=2*4*st which is 8st BUT 2s+4t=2s+4t

BTWFYI, I am Owen.

ReplyDeleteSorry. :)

No,Jane is wrong. 3a is different from b so these two terms cannot be simplified as 3ab when added together.Similarly, 2s is also different from 4t so the coefficients and the variables cannot be add together.

ReplyDeleteEg: let a be 3 and b be 4

1. 3a+b=3*3+4 2. 3ab=3*3*4

=9+4 =36

=13

The values are different.

Eg: let s be 5 and t be 6

1. 2s+4t=2*5+4*6 2. 6st=6*5*6

=10+24 =180

=34

The values are different.

Correct answers

1. 3a+b=3a+b 2. 2s+4t=2s+4t

No, she is wrong.

ReplyDelete3a + b=3a+b

She took a x b, but in this case the equation is addition, so she cannot multiply them.

2s + 4t=2s+4t

She took 2+4, and s + t. For the first part, the values of the unknowns are different, so she cannot add the coefficients together. The equation is addition, but she took s x t, which is wrong.